Prostatic cyst in general practice: A case report and literature review. Issue 9 (March 2018) - Qiu, Yan; Liu, Ying; Ren, Wen; Ren, Jingjing
Abstract: Rationale: Prostatic cyst is a rare disease of the prostate especially in general practice. As it is often asymptomatic, how to manage it is still unfamiliar with, general practitioners (GPs). Patient concerns: The 24-year-old man presented with left back discomfort for 1 week without severe pain, dysuria, or fever. Diagnoses: Ultrasonography revealed the presence of a 14×14 mm cystic lesion. Interventions: The patient was given the medicine and regular follow-up. Outcomes: Several days later, he recovered without lower back discomfort. Lessons: Patients with prostatic cyst of small size and no symptom should be follow-up regularly. Although prostatic cyst of progressive symptoms, large size (2.5 cm or larger), or high serum prostate-specific antigen (PSA) should be timely referred to urological specialists.